Quantifying meat spoilage: Ethic fresh as a portable halal-tayyibah screening innovation - Erlina Nur Arifani; Sevia Indah Purnama; Mas Aly Afandy; Danny Kurnianto (Nur Science Institute, 2026)
The complexity of today's global food supply chain poses significant challenges for detecting meat spoilage, creating a pressing need to protect consumers who adhere to Halal-Tayyibah principles, especially when human visual/sensory inspection fails to detect the early stages of spoilage. To address this issue, Ethic Fresh was designed using an experimental engineering approach that integrates a calibrated electrochemical ammonia sensor, an RGB optical color sensor, and a threshold classification algorithm into a portable, non-destructive device connected to a digital data logger. The design results demonstrated that Ethic Fresh has high classification sensitivity and accuracy, successfully classifying chicken meat into three Halal-Tayyibah status categories: Fresh (low ammonia, high R-value; Full Thayyib), Semi-Fresh (oxidation crisis threshold; Doubtful/Warning), and Spoiled (high ammonia, low R-value; Khaba'ith). While not a substitute for formal laboratory testing, its portability and rapid response time make Ethic Fresh a highly viable screening tool for daily use in the market, helping consumers make safe and Halal food decisions while supporting the Halal 4.0 digital supply chain ecosystem.